Parental perception on home therapy and its associated factors for children with cerebral palsy: a qualitative study in Malaysia - Chandrabose, Thanalactchumy; Suppiah, Subapriya; Romli, Muhammad Hibatullah; Engkasan, Julia Patrick; Ahmad Fauzi, Aishah (Malaysian Medical Association, 2024)
Introduction: Children with cerebral palsy (CP) benefit from consistent rehabilitation intervention. Home therapy (HT) consists of therapeutic exercises and activities targeting physical and functional improvement. HT is vital to ensure the rehabilitation provided in the clinical setting is further continued by the client. However, the success of HT mostly depends on compliance and support from caregivers, especially the parents. The objective of this study was to explore parents' perceptions of home therapy and to identify facilitating factors and barriers to it. Materials and Methods: An interview-based qualitative study was conducted in a public university hospital in Malaysia, utilizing in-depth interviews. Audio recordings of the interviews were transcribed verbatim. The transcript data were coded, and the codes were then organized into themes using a thematic analysis approach. Results: Data from twelve mothers and three fathers among a total of fifteen children with CP were acquired. Nine themes were derived from transcript data namely : HT is a simple home prescription,HT empowers and enhances experiences of care, Negative experience, goal-directed positive attitude, External Support System, physical health as a barrier, psychological health as barrier, limited time and limited external support system. Conclusion: Real-life experiences of parents with CP children regarding HT was explored and valuable outcomes were derived from this study to help clinicians to manage children with CP more efficiently and understand their family dynamics better in the local context. Overall, parents perceived HT as doable and it provided physical, functional, and psychological benefits for them as well as improved their confidence and skills to perform exercises on their children and empowered them to monitor their children's progression.